Flux-cored wire for welding duplex stainless steel

JP7651348B2Active Publication Date: 2025-03-26NIPPON STEEL WELDING & ENGINEERING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021057352
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-26
Estimated Expiration
2041-03-30

Smart Images

  • Figure 0007651348000006
    Figure 0007651348000006
  • Figure 0007651348000001
    Figure 0007651348000001
  • Figure 0007651348000002
    Figure 0007651348000002
Patent Text Reader

Abstract

To provide a flux-cored wire for welding two-phase stainless steel that provides a good weld metal and has an excellent defect-resistance performance.SOLUTION: A flux-cored wire for welding two-phase stainless steel contains Si: 0.10-0.90%, Mn: 0.5-2.0%, Ni: 7-11%, Cr: 22-27%, Mo: 0.1-4.0%, Ti: 0.2-1.2%, Co: 0.01-0.30%, and N: 0.08-0.20% by %mass of the total mass of the wire in terms of the total of a stainless steel sheath and a flux, and further contains TiO2 conversion value: 3-9%, SiO2 conversion value: 0.5-3.0%, F conversion value: 0.1-0.5%, Na2O conversion value and K2O conversion value: 0.1-1.0%, and Bi conversion value: 0.01-0.06% by %mass of the total mass of the wire in the flux at C: 0.04% or less and Cu: 0.5% or less, and is characterized in that a PRE value is 28 to 37 at Al2O3 conversion value: 0.1% or less, and Zr conversion value: 0.1% or less. PRE=[Cr]+3.3[Mo]+[N].SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flux-cored wire for welding duplex stainless steel, which is used for welding duplex stainless steel, and which can produce a weld metal having strength comparable to that of the base metal, as well as good low-temperature toughness and corrosion resistance, and which has excellent resistance to defects such as blowholes, and which also has good welding workability, such as a stable arc and low amount of spatter generation. [Background technology]

[0002] Duplex stainless steels have both austenite and ferrite phases in their metal structure, and are characterized by a lower Ni content and higher strength than austenitic stainless steels. The pitting corrosion resistance of duplex stainless steels is classified using pitting corrosion resistance indices PRE (Cr+3.3Mo+16N) and PREW (Cr+3.3(Mo+0.5W)+1.6N) based on the mass percentages of Cr, Mo, N, and W contained in their chemical composition structure. Conventional duplex stainless steels such as SUS329J3L and SUS329J4L are steel plates with higher pitting corrosion resistance than the highly corrosion-resistant austenitic general-purpose stainless steel SUS316L, but contain a large amount of expensive Mo, which increases the alloy cost, and they are used for applications that require particularly high corrosion resistance, such as chemical tanker materials.

[0003] In recent years, inexpensive alloy-saving duplex stainless steels with low pitting corrosion resistance index PRE have been developed as replacements for austenitic stainless steels SUS304 and SUS316L. Alloy-saving duplex stainless steels are steels that have low alloying by replacing expensive Ni and Mo with Cr, Mn and N, while suppressing corrosion resistance to the same level as SUS304 and SUS316L stainless steels. As such, duplex stainless steels have superior properties such as high corrosion resistance and high strength compared to austenitic stainless steels SUS304 and SUS316L, and are widely used in infrastructure facilities such as structural members in the civil engineering field, dam structural members and water gates. On the other hand, applicable welding materials are required to have a corrosion resistance index equal to or higher than those of these steels, and to be inexpensive and have good weld metal performance and welding workability.

[0004] In this situation, there is a need for the development of a flux-cored wire that can weld with high efficiency and good welding workability in all positions. However, when welding duplex stainless steel, which contains a lot of N, there is a problem that welding defects such as blowholes occur. In addition, there is a problem that the bead shape tends to be convex in vertical upward welding, which requires an additional process of touching up with a grinder.

[0005] As a technique for solving such problems, for example, Patent Document 1 specifies C, Si, Mn, Ni, Cr, Mo, Ti, N, and Cu, and specifies TiO as a slag agent. 2 Conversion value, SiO 2 Conversion value, ZrO 2 Conversion value, Al 2 O 3 In this publication, a flux-cored wire is disclosed that has excellent strength and toughness, good resistance to porosity defects such as blowholes, good corrosion resistance, and excellent all-position weldability, with the F-converted value and F-converted value specified. However, this flux-cored wire has problems such as poor welding workability, with an unstable arc, a large amount of spatter generation, and poor slag removability.

[0006] In addition, Patent Document 2 specifies C, Si, Mn, Ni, Cr, Mo, Ti, Al, N, and Cu, and specifies TiO as a slag agent. 2 Conversion value and SiO 2 Conversion value, ZrO 2 Conversion value, Al 2 O 3 Conversion value, F conversion value, Bi conversion value, Na 2 O and K 2 A flux-cored wire for welding duplex stainless steel has been disclosed, which has a regulated O-converted value, provides a weld metal with strength and toughness comparable to that of the base metal, excellent resistance to porosity defects such as blowholes, good resistance to pitting corrosion, and good welding workability in all positions. However, even with this flux-cored wire, there are problems such as an unstable arc and a large amount of spatter generation, which make it difficult to obtain good welding workability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-131912 A [Patent Document 2] JP 2018-130762 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a flux-cored wire for welding duplex stainless steel, which is used for welding duplex stainless steel, can produce a weld metal having strength comparable to that of the base metal, and excellent low-temperature toughness and corrosion resistance, and which has excellent resistance to defects such as blowholes, and also has good welding workability, such as a stable arc and low amount of spatter generation. [Means for solving the problem]

[0009] The gist of the present invention is a flux-cored wire for welding duplex stainless steel, which is formed by filling a stainless steel sheath with flux, and which contains, in mass % relative to the total mass of the wire, the total of the stainless steel sheath and the flux: Si: 0.10-0.90%, Mn: 0.5-2.0%, Ni: 7-11%, Cr: 22-27%, Mo: 0.1-4.0%, Ti: 0.2-1.2%, Co: 0.01-0.30%, N: 0.08-0.20%, C: 0.04% or less, and Cu: 0.5% or less. Furthermore, in mass % relative to the total mass of the wire, the flux contains Ti oxide TiO 2 Total conversion value: 3-9%, SiO of Si oxide 2 Total of F-converted values: 0.5 to 3.0%, Total of F-converted values ​​of metal fluorides: 0.1 to 0.5%, One or more of Na oxide, Na fluoride, K oxide and K fluoride: Na 2 O conversion value and K 2 O equivalent value of 0.1 to 1.0% in total, Bi and / or Bi oxide: Bi equivalent value of 0.01 to 0.06% in total, Al oxide: 2 O 3 Total of converted values: 0.1% or less, ZrO 2The total of the converted values ​​is 0.1% or less, the PRE value calculated from the following formula (1) for the contents of Cr, Mo, and N is 28 to 37, and the remainder is Fe in the stainless steel sheath, iron powder in the flux, Fe from the iron alloy, and unavoidable impurities. PRE=[Cr]+3.3[Mo]+16[N]···(1) (Note that [Cr], [Mo], and [N] are the mass % of the total wire mass.)

[0010] The flux-cored wire for welding duplex stainless steel is also characterized in that, in terms of mass % relative to the total mass of the wire, the total content of Mn in the stainless steel sheath and flux is 0.5 to less than 1.0%. Effect of the Invention

[0011] According to the flux-cored wire for welding duplex stainless steel of the present invention, in welding duplex stainless steel, a weld metal having strength comparable to that of the base metal, and good low-temperature toughness and corrosion resistance can be obtained, and a flux-cored wire for welding duplex stainless steel can be provided which has excellent resistance to defects such as blowholes, and has good welding workability such as a stable arc and a small amount of spatter. [Brief description of the drawings]

[0012] [Figure 1] FIG. 13 is a diagram showing an example of evaluating arc stability by measuring voltage fluctuations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In order to improve the strength, toughness and corrosion resistance of the weld metal, the inventors conducted detailed studies on the component composition of a flux-cored welding wire that is based on a component system that adjusts Ni and Cr to obtain a dual-phase structure in which austenite and ferrite remain, and that provides excellent welding work with a smooth bead shape even in all-position welding, a stable arc, little spatter generation, good slag removability and good bead shape.

[0014] As a result of examining the content of Cr, a ferrite-forming element, it was found that as the Cr content in the weld metal increases, the amount of ferrite crystallized increases, resulting in a two-phase structure in which austenite precipitates within the ferrite grains, resulting in a stable and high strength structure. On the other hand, when the Cr content exceeds the appropriate amount, the amount of austenite precipitates decreases, and the nitrogen that was dissolved in austenite remains in a supersaturated state in the ferrite phase. As a result, problems such as the formation of Cr nitrides due to reheating during welding and the deterioration of toughness occurred. Therefore, it was found that the austenite structure can be made more stable and toughness can be improved by adding Ni to suppress Cr nitrides and precipitate an appropriate amount of austenite phase, which has a higher solid solubility than the ferrite phase. It was found that the corrosion resistance can be improved by stabilizing the austenite structure of the weld metal by adjusting the contents of Ni, Cr, Mo, and N to the appropriate amounts, and further limiting the contents of Cr, Mo, and N can further improve the corrosion resistance.

[0015] It was also found that the arc stability could be improved by adding appropriate amounts of Co, Si oxide, Na oxide, Na fluoride, K oxide and K fluoride, and the amount of spatter generation could be reduced by adding appropriate amounts of metal fluorides and reducing the amount of Mn added.

[0016] Furthermore, it was confirmed that as the amount of N increases, welding slag remains on some of the bead surface, which reduces slag removability. It was found that reducing Zr oxide, a slag component, can improve slag removability.

[0017] The present invention has been made possible by the synergistic effects of the individual and coexisting components of the stainless steel sheath and the filled flux, but the reasons for adding and limiting each component are described below. The content of each component is expressed in mass%, and the description of mass% is simply expressed as %.

[0018] [Stainless steel sheath and flux combined: 0.10-0.90% Si] Silicon is added from the stainless steel outer skin, metal silicon, Fe-Si, Fe-Si-Mn, etc., and has the effect of improving defect resistance such as blowholes by deoxidizing. If the silicon content is less than 0.10%, the deoxidizing effect is not obtained, and pore defects such as blowholes are likely to occur. On the other hand, if the silicon content exceeds 0.90%, low melting point compounds are generated, making hot cracks more likely to occur. Therefore, the silicon content is set to 0.10 to 0.90%.

[0019] [Mn: 0.5-2.0% in total for stainless steel sheath and flux] Mn is added from stainless steel sheath, metallic Mn, Fe-Mn, Fe-Si-Mn, Mn nitride, etc., and has the effect of fixing S in the weld metal as MnS and improving hot cracking resistance. If Mn is less than 0.5%, sufficient hot cracking resistance cannot be obtained. On the other hand, if Mn exceeds 2.0%, the amount of spatter generation increases. Therefore, Mn is set to 0.5 to 2.0%.

[0020] Furthermore, the amount of spatter can be further reduced by reducing the Mn content, and the Mn content is preferably set to 0.5 to less than 1.0%.

[0021] [Stainless steel sheath and flux combined: 7-11% Ni] Ni is added as a component contained in the stainless steel sheath, as metallic Ni and Fe-Ni from the flux, and has the effect of stabilizing the austenite phase to improve corrosion resistance and toughness of the weld metal. If Ni is less than 7%, the amount of austenite precipitated is small and the nitrogen that was dissolved in austenite remains in the ferrite phase in a supersaturated state, so that Cr nitrides are formed by reheating during welding, and the corrosion resistance and toughness of the weld metal are reduced. On the other hand, if Ni exceeds 11%, the amount of austenite crystallized increases and the strength of the weld metal is reduced. Therefore, Ni is set to 7-11%.

[0022] "The total of the stainless steel sheath and flux is 22-27% Cr." Cr is added as a component contained in the stainless steel sheath, as metallic Cr, Fe-Cr, Cr nitride, etc. from the flux, and has the effect of stabilizing the ferrite phase of the weld metal and improving corrosion resistance and strength. If the Cr content is less than 22%, the corrosion resistance and strength of the weld metal cannot be sufficiently obtained. On the other hand, if the Cr content exceeds 27%, the amount of ferrite crystallized in the weld metal increases, and embrittled structures such as σ phase are precipitated, reducing toughness. Therefore, the Cr content is set to 22-27%.

[0023] [Total of stainless steel sheath and flux: Mo: 0.1-4.0%] Mo is added as metallic Mo and Fe-Mo from flux, in addition to being a component contained in the stainless steel sheath, and has the effect of improving the corrosion resistance of the weld metal and the effect of improving strength by solid solution strengthening. If Mo is less than 0.1%, the weld metal cannot obtain sufficient corrosion resistance and strength. On the other hand, if Mo exceeds 4.0%, embrittled structures such as σ phase are precipitated in the weld metal, reducing toughness. Therefore, Mo is set to 0.1 to 4.0%.

[0024] [Total of stainless steel sheath and flux: Ti: 0.2-1.2%] Ti is added from metallic Ti and Fe-Ti in the flux as well as from the stainless steel sheath, and has the effect of improving defect resistance such as blowholes by deoxidizing. If Ti is less than 0.2%, the deoxidizing effect is not obtained and pore defects such as blowholes are likely to occur. On the other hand, if Ti is more than 1.2%, droplet transfer does not proceed smoothly, and the droplets grow large and transfer, making the arc unstable. Therefore, Ti is set to 0.2 to 1.2%.

[0025] [Total of stainless steel sheath and flux: Co: 0.01~0.30%] Co is added as a component contained in the stainless steel sheath, as metallic Co and Fe-Co from the flux, and has the effect of adjusting the ionization voltage and improving the arc stability. If the Co content is less than 0.01%, sufficient arc stability cannot be obtained. On the other hand, if the Co content exceeds 0.30%, the toughness of the weld metal decreases. Therefore, the Co content is set to 0.01 to 0.30%.

[0026] [N: 0.08~0.20% in total for stainless steel sheath and flux] N is added from the flux as Cr nitride and Mn nitride, as well as from the stainless steel sheath, and stabilizes the austenitic structure of the weld metal. It is also a solid solution strengthening element that increases the strength of the weld metal and improves corrosion resistance. If N is less than 0.08%, the weld metal will not have sufficient strength and corrosion resistance. On the other hand, if N exceeds 0.20%, slag will stick and slag removability will be poor.

[0027] [Stainless steel outer sheath and flux combined C: 0.04% or less] C is added from metal powder and iron alloys in flux, as well as being a component of the stainless steel sheath. It has the effect of improving the strength of the weld metal. However, if added in excess, it combines with Cr and Mo, etc. to form carbides, which reduce the toughness of the weld metal, so the content should be 0.04% or less.

[0028] [Stainless steel sheath and flux combined Cu: 0.5% or less] Cu is an element contained in the stainless steel sheath, and is also added from metallic Cu in the flux, etc. Adding a small amount of Cu has the effect of stabilizing the austenitic structure of the weld metal and improving toughness, but adding too much of it reduces resistance to hot cracking, so the amount should be 0.5% or less.

[0029] [TiO in the flux] 2 Total conversion value: 3-9% Titanium oxide has the effect of adjusting the amount of slag generated by the arc and its melting point, and improving the bead shape during vertical upward welding. 2 If the total of the converted values ​​is less than 3%, a sufficient amount of slag cannot be obtained, making it difficult to hold the molten metal during vertical upward welding, resulting in a convex bead shape. 2 If the total of the converted values ​​exceeds 9%, the amount of slag generated during welding becomes excessive, and the slag encapsulation becomes poor. 2The total of the converted values ​​is 3 to 9%. Note that Ti oxide can be added from rutile, titanium oxide, titanium slag, ilmenite, potassium titanate, sodium titanate, etc. from flux.

[0030] [SiO of Si oxide in flux 2 Total conversion value: 0.5-3.0% Silicon oxide has the effect of adjusting the droplet transfer interval and improving the arc stability. 2 If the total of the converted values ​​is less than 0.5%, the droplets grow too large and sufficient arc stability cannot be obtained. 2 If the total of the converted values ​​exceeds 3.0%, the slag removability becomes poor. 2 The total of the converted values ​​should be 0.5 to 3.0%. Silicon oxide can be added from silica sand and silica stone from the flux, as well as from potassium feldspar, zircon sand, sodium silicate, etc.

[0031] [Total F-equivalent value of metal fluorides in flux: 0.1-0.5%] Metal fluorides have the effect of smoothing droplet transfer and reducing the amount of spatter generation. If the total F-converted value of the metal fluorides is less than 0.1%, the effect of reducing the amount of spatter generation during droplet transfer cannot be obtained. On the other hand, if the total F-converted value of the metal fluorides exceeds 0.5%, the melting point of the slag decreases and the bead shape becomes poor. Therefore, the total F-converted value of the metal fluorides is set to 0.1 to 0.5%. The metal fluorides are NaF, LiF, CaF 2 , AlF 3 , K 2 ZrF 6 , K 2 SiF 6 etc., and the F equivalent value is the sum of the F contents contained therein.

[0032] [One or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride in flux: Na 2 O conversion value and K 2 Total O equivalent value: 0.1-1.0% Na oxide, Na fluoride, K oxide and K fluoride have the effect of improving the arc stability. 2 O conversion value and K 2 If the total O equivalent value is less than 0.1%, sufficient effect is not obtained and the arc becomes unstable. On the other hand, if one or more of Na oxide, Na fluoride, K oxide and K fluoride are used, 2 O conversion value and K 2 If the total O conversion value exceeds 1.0%, the amount of spatter generation increases. Therefore, Na oxide, Na fluoride, K oxide, and K fluoride are used as the Na oxide, Na fluoride, K oxide, and K fluoride. 2 O conversion value and K 2 The total O-equivalent value is 0.1 to 1.0%. Na oxide and K oxide are solid components of water glass made of sodium silicate and potassium silicate, potassium feldspar, and soda feldspar, while Na fluoride and K fluoride are NaF, KF, and K 2 SiF 6 , Na 2 AlF 6 It can be added in the form of powder.

[0033] [Bi and / or Bi oxide in the flux: 0.01 to 0.06% in total in terms of Bi] Bi has the effect of improving slag removability. If the total of the Bi-equivalent values ​​of one or both of Bi and Bi oxide is less than 0.01%, slag sticking occurs and sufficient slag removability cannot be obtained. On the other hand, if the total of the Bi-equivalent values ​​of one or both of Bi and Bi oxide exceeds 0.06%, a low melting point compound is generated during solidification, and hot cracking resistance deteriorates. Therefore, the total of the Bi-equivalent values ​​of one or both of Bi and Bi oxide is set to 0.01 to 0.06%. Bi and Bi oxide can be added from metal powder such as metal Bi, Bi oxide, etc.

[0034] [Al oxide in flux 2 O 3 Total conversion value: 0.1% or less Al oxide is contained as an impurity in the flux, such as Ti oxide, potassium feldspar, and silica sand. 2 O3 If the total of the converted values ​​exceeds 0.1%, the amount of slag increases, and the slag encapsulation property deteriorates.

[0035] [Zr oxide in flux, ZrO 2 Total conversion value: 0.1% or less Zr oxide is inevitably contained as an impurity in Ti oxide, potassium feldspar, and silica sand. It has a high affinity with N, and when its content exceeds 0.1%, it bonds with N to generate a strong slag, which causes the slag to stick to the bead surface and reduces the slag removability. Therefore, Zr oxide, ZrO 2 The total of the converted values ​​shall not exceed 0.1%.

[0036] [The PRE value calculated from formula (1) for the contents of Cr, Mo, and N is 28 to 37] PRE=[Cr]+3.3[Mo]+16[N]···(1) (Note that [Cr], [Mo], and [N] are the mass % of the total wire mass.) The PRE value is an index of the pitting corrosion resistance of duplex stainless steel based on the mass percentage of Cr, Mo, N, etc. contained in its chemical composition structure, and is called the pitting corrosion resistance index (PRE). If the PRE value is less than 28, the weld metal will not have sufficient corrosion resistance. On the other hand, if the PRE value exceeds 37, the toughness of the weld metal will decrease. Therefore, the PRE value should be 28 to 37.

[0037] The remainder of the flux-cored wire for duplex stainless steel welding of the present invention is Fe in the stainless steel sheath, iron powder added from the flux to adjust the composition, Fe content from iron alloys such as Fe-Si, Fe-Mn, Fe-Si-Mn, Fe-Ni, Fe-Cr, Fe-Mo, Fe-Co, Fe-Ti alloys, and impurities. There are no particular limitations on the impurities, but it is preferable that P is 0.040% or less and S is 0.030% or less in order to ensure strength and toughness.

[0038] Regarding the manufacturing method of the flux-cored wire for welding duplex stainless steel of the present invention, for example, when the sheath is formed into a tubular shape from a steel strip, the flux is mixed, stirred, and dried and filled into a U-shaped groove, which is then formed into a round shape and drawn to a predetermined wire diameter. At this time, the shaped sheath seam can be welded to produce a seamless flux-cored wire. When the sheath is a pipe, the pipe is vibrated to fill the flux, and the wire is drawn to a predetermined wire diameter.

[0039] The flux filling may be granulated by adding an adhesive (aqueous solution of potassium silicate and sodium silicate) to facilitate smooth supply and filling. The flux filling rate is not particularly limited, but is preferably 18 to 28% of the total wire mass from the viewpoint of productivity. EXAMPLES

[0040] The present invention will now be described in detail with reference to examples.

[0041] Using an austenitic stainless steel sheath with the chemical composition shown in Table 1, flux-cored wires for welding duplex stainless steel with various compositions shown in Table 2 were produced. The wire diameter was 1.2 mm, and the flux filling rate was 20 to 26% of the total wire mass.

[0042] [Table 1]

[0043] [Table 2]

[0044] These prototype wires were used to investigate the deposited metal test, porosity resistance, cracking resistance, corrosion resistance and welding workability.

[0045] The weld metal test was performed using duplex stainless steel with the steel plate designation B1 shown in Table 3, in accordance with JIS Z 3111, under the welding conditions for T1 shown in Table 4. After welding, an X-ray examination was performed based on JIS Z 3106 to check for the occurrence of porosity and cracks in the welds.

[0046] [Table 3]

[0047] [Table 4]

[0048] The performance of the weld metal was evaluated by taking tensile test pieces (A0 size) and impact test pieces (V-notch test pieces) from the center of the plate thickness direction of the weld metal, and conducting tensile tests and impact tests. Tensile strength was evaluated as good if it was 690MPa or more. Impact tests were evaluated by conducting Charpy impact tests at -20℃ for three pieces each, and an average absorbed energy of 27J or more was evaluated as good.

[0049] In the X-ray test, a specimen was rated as good if it had less than three blowhole-like defects of the first kind. In addition, the specimen was rated as good if it had no third-kind defects similar to hot cracks.

[0050] For the evaluation of corrosion resistance, a corrosion test was performed on the welded specimen after the weld metal test in accordance with the ASTM G48 METHODE, and a critical pitting temperature (hereinafter referred to as CPT) of 25°C or higher was considered to be good.

[0051] To evaluate the welding workability, first, a bead-on-plate welding test was carried out under welding conditions T2 in Table 4, using duplex stainless steel with steel plate designation B2 shown in Table 3 to measure the amount of spatter generated and the stability of the arc. The amount of spatter generated was measured using a copper collection box to measure the amount of spatter generated during welding for 1 minute, and the value per unit time (g / min) was calculated. The spatter measurement was taken as the average value of 5 measurements, with 1g / min or less being considered good. The stability of the arc was evaluated based on the magnitude of the voltage, measuring the voltage fluctuation 5 times for 10 seconds while measuring the amount of spatter generated. As shown in the time-series voltage fluctuation chart in Figure 1(a), the evaluation was based on the time during which the voltage fluctuation exceeded the threshold value, with a threshold value of ±1V from the average voltage, within the measurement time (50 seconds). 10 %, the arc is deemed stable. On the other hand, as shown in the time-series voltage fluctuation chart in Figure 1(b), when the threshold is set to ±1V from the average voltage, if the time during which the voltage fluctuation exceeds the threshold exceeds 10% within the measurement time (50 seconds), the arc is deemed unstable.

[0052] Regarding other welding workability, horizontal fillet welding was performed under welding condition T3 in Table 4 and vertical upward welding under welding condition T4 using duplex stainless steel with steel plate symbols B1 and B2 shown in Table 3, and the slag encapsulation, slag removability, and bead shape were investigated.

[0053] Slag encapsulation was evaluated by estimating the area of ​​the bead that was visually free of slag, and a bead free of 10% or less was rated as good. Slag removability was evaluated after welding by using a chipping hammer (total length 300 mm, weight 350 g) to strike the solidified slag on the surface of the weld bead by lightly swinging it down in an arc around the handle. If the slag cracked and could then be easily removed with a brush, it was rated as good, and if the slag adhered to the bead surface and could not be removed, it was rated as poor. Bead shape was rated as good if there were no undercuts or overlaps that would require rework in the healthy part of the weld bead. The results are summarized in Table 5.

[0054] [Table 5]

[0055] Wire Nos. 1 to 16 in Tables 2 and 5 are examples of the present invention, and Wire Nos. 17 to 32 are comparative examples. Wire Nos. 1 to 16, which are examples of the present invention, are made of Si, Mn, Ni, Cr, Mo, Ti, Co, N, C, Cu, Ti oxide TiO 2 The sum of the converted values ​​of Si oxides, SiO 2 Sum of F-converted values ​​of metal fluorides, Sum of F-converted values ​​of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride 2 O conversion value and K 2 Sum of O equivalents, Sum of Bi equivalents of either or both of Bi and Bi oxides, Al of Al oxides 2 O 3 The sum of the converted values ​​of Zr oxides, ZrO 2 The total of the converted values ​​and the PRE value were appropriate, so the tensile strength and absorbed energy of the deposited metal were good, and in the X-ray transmission test, the number of Class 1 defects was low, so the pitting corrosion resistance was good, and there were no Class 3 defects, so the cracking resistance was good, and the CPT was 25°C or higher, so the corrosion resistance was also good. In addition, the amount of spatter generation was low, so the arc stability was good. Furthermore, the slag encapsulation, slag removability, and bead shape were also good in horizontal fillet and vertical upward welding.

[0056] In addition, in wires No. 1 to 4, No. 6, No. 8, No. 10, No. 12, No. 13 and No. 16, which had Mn contents of less than 1.0%, the amount of spatter generated was 0.6 g / min or less, which was an extremely satisfactory result.

[0057] In the comparative example, wire No. 17 had a low absorbed energy of the deposited metal because of the high C content, and had a low N content, so the tensile strength of the deposited metal was low, the CPT temperature was low, and the corrosion resistance was also poor.

[0058] Wire No. 18 had low absorbed energy of the deposited metal because of the high Co content, and had poor slag removability because of the high N content.

[0059] Wire No. 19 has a low Si content, so it had a high score for type 1 scratches in the X-ray examination. In addition, it had a high score for one or more of the following Na oxides, Na fluorides, K oxides, and K fluorides. 2 O conversion value and K 2 The total O conversion value was small, so the arc was unstable.

[0060] Wire No. 20 has a high Si content, so three types of defects indicating high temperature cracking were observed in the X-ray examination. In addition, the following defects were observed: Na oxide, Na fluoride, K oxide, and K fluoride. 2 O conversion value and K 2 The total O equivalent value was high, so there was a lot of spatter generation.

[0061] Wire No. 21, which contains a small amount of Mn, showed three types of defects indicating high temperature cracking in the X-ray examination. 2 Since the total converted value was large, the slab peelability was poor.

[0062] Wire No. 22 had a large amount of Mn, so it generated a large amount of spatter. 2 O 3 Since the total converted value was high, the slag encapsulation was poor.

[0063] Wire No. 23 had a low Ni content, so the absorbed energy of the deposited metal was low, the CPT temperature was low, and the corrosion resistance was poor. In addition, the total F-converted value of the metal fluorides was low, so the amount of spatter was high.

[0064] Wire No. 24 had a high Ni content, so the tensile strength of the deposited metal was low. Also, the total F-converted value of metal fluorides was high, so the bead shape was poor.

[0065] Wire No. 25 had a low Cr content, so the tensile strength of the deposited metal was low, the CPT temperature was low, and the corrosion resistance was poor. In addition, the SiO 2 Because the total converted value was small, the arc was unstable.

[0066] Wire No. 26 had a high Cr content, so the absorbed energy of the weld metal was low. Also, the Si oxide SiO 2 Since the total converted value was large, the slag removability was poor.

[0067] Wire No. 27 had a low Mo content, so the tensile strength of the deposited metal was low, the CPT temperature was low, and the corrosion resistance was poor. In addition, Ti oxide TiO 2 Because the converted value was small, the bead shape was poor.

[0068] Wire No. 28 had a high Mo content, so the absorbed energy of the weld metal was low. Also, the Ti oxide TiO 2 Since the conversion value was high, the slag encapsulation was poor.

[0069] Wire No. 29 had a low Ti content, so it had a high score of type 1 defects in the X-ray examination. In addition, because the PRE value was low, the CPT of the deposited metal was also low in temperature and the corrosion resistance was poor.

[0070] Wire No. 30 had an unstable arc due to its high Ti content, and also had a high Cu content, which resulted in three types of defects indicating high temperature cracks in the X-ray examination.

[0071] Wire No. 31 had poor slag removability because the total of either or both of the Bi-equivalent values ​​of Bi and Bi oxide was low. Also, the PRE value was high, so the absorbed energy of the deposited metal was low.

[0072] Wire No. 32 had an unstable arc because of the small amount of Co. Also, because the total of the Bi-equivalent values ​​of one or both of Bi and Bi oxide was high, three types of defects indicating high-temperature cracks were generated in the X-ray transmission test.

Claims

1. In a flux-cored wire for welding duplex stainless steel, the flux is filled in a stainless steel sheath, The total mass of the stainless steel sheath and flux is expressed as a percentage by mass of the total mass of the wire. Si: 0.10-0.90%, Mn: 0.5-2.0%, Ni: 7 to 11%, Cr: 22-27%, Mo: 0.1 to 4.0%, Ti: 0.2-1.2%, Co: 0.01 to 0.30%, N: 0.08 to 0.20%; C: 0.04% or less, Cu: 0.5% or less; Furthermore, in the flux, the mass percentage relative to the total mass of the wire is: Ti oxide TiO 2 Total conversion value: 3-9%, Silicon oxide SiO 2 Total conversion value: 0.5-3.0%, Total F-converted value of metal fluorides: 0.1 to 0.5%, One or more of Na oxide, Na fluoride, K oxide and K fluoride: Na 2 O conversion value and K 2 Total O equivalent value: 0.1 to 1.0% One or both of Bi and Bi oxide: Contains 0.01 to 0.06% in total in terms of Bi, Al oxide Al 2 O 3 Total of converted values: 0.1% or less, Zr oxide ZrO 2 Total conversion value: 0.1% or less, The flux-cored wire for welding duplex stainless steel is characterized in that the contents of Cr, Mo, and N are such that the PRE value calculated from the following formula (1) is 28 to 37, and the balance is Fe in the stainless steel sheath, iron powder in the flux, Fe from the iron alloy, and impurities. PRE=[Cr]+3.3[Mo]+16[N]...(1) (where [Cr], [Mo] and [N] are mass % relative to the total mass of the wire)

2. The total mass of the stainless steel sheath and flux is expressed as a percentage by mass of the total wire mass. The flux-cored wire for welding duplex stainless steel according to claim 1, characterized in that Mn is 0.5 to less than 1.0%.

Citation Information

Patent Citations

  • Flux cored wire for welding duplex stainless steel

    JP2008221292A

  • Flux-cored wire for stainless steel arc welding

    JP2011125875A

  • Flux cored wire for welding stainless steel

    JP2015120174A

  • Flux-cored wire for two-phase stainless steel welding

    JP2017131912A

  • Flux-cored wire for welding duplex stainless steel

    JP2018130762A